PENJABARAN HAK TENAGA KERJA PEREMPUAN ATAS UPAH DAN WAKTU KERJA DALAM PERATURAN PERUSAHAAN DAN PERJANJIAN KERJA - Fitriani, Diah (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 4 No 2 (2015), 2015)
This study aims to identify and analyze the importance of normative Rights of workers, especially women workers. This study is an empirical law with a field study observation approach to the way to the destination research. data and data sources consist of primary legal materials, secondary law and tertiary legal materials were analyzed by using interviews with informants and respondents. Based on the Law of the Republic of Indonesia Number 13 of 2003 on Labour, the protection of women workers to ensure the basic rights of workers, and ensure equality of opportunity and treatment without discrimination on the basis of apaun for the welfare of women workers and their families with regard to the progress the business world, the rules made in the company regulations that sesusi with the legislation in force will have an impact on the welfare of workers and the development of the company, as well as the rights and obligations of the parties between workers and the company shall set forth in writing and in detail, in order to no problems in the future.
Keywords: basic rights of women workers in conformity with human rights requirements